2016
DOI: 10.1039/c5ra23547b
|View full text |Cite
|
Sign up to set email alerts
|

Design and fabrication of a graphene/carbon nanotubes/activated carbon hybrid and its application for capacitive deionization

Abstract: Novel three-component graphene/carbon nanotubes/activated carbon (GTAC) hybrids were prepared and investigated as capacitive deionization electrode, and as-prepared GTAC-20 hybrid exhibits a high elcetrosorption capacity of 2.30 mg g−1 and good repeatability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Thus, it can be assumed that when using composite aerogels as electrodes for MCDI under the tested conditions, the diffusion processes in a porous monolith do not limit the rate of deionization of water. The average value of the electrosorption capacity calculated from the experimental data presented in Figure 13 per unit mass of dry aerogel is 25.3 mg/g, which also exceeds that obtained in previously published works [16,18].…”
Section: Surface and Some Other Properties Of Composite Aerogelssupporting
confidence: 58%
See 1 more Smart Citation
“…Thus, it can be assumed that when using composite aerogels as electrodes for MCDI under the tested conditions, the diffusion processes in a porous monolith do not limit the rate of deionization of water. The average value of the electrosorption capacity calculated from the experimental data presented in Figure 13 per unit mass of dry aerogel is 25.3 mg/g, which also exceeds that obtained in previously published works [16,18].…”
Section: Surface and Some Other Properties Of Composite Aerogelssupporting
confidence: 58%
“…The process is completely symmetrical, which indicates the reversibility of electrosorption and desorption. The specific capacity for the sorbed salt (per 1 g of dry electrode material) calculated from these curves is 62 mg/g, and this value, taking into account the equilibrium concentration of salt in a liquid phase, exceeds all known and previously published capacitance values [16][17][18]. We can consider how the same electrodes work in dynamic mode.…”
Section: Surface and Some Other Properties Of Composite Aerogelsmentioning
confidence: 83%
“…Many studies have demonstrated that carbon-based materials can meet the requirements of high performance CDI electrodes, such as activated carbon, porous carbon, carbon nanotubes, graphene and their composites with inorganic materials. [14][15][16][17][18][19][20][21][22][23][24][25][26][27] However, almost all carbon-based materials for CDI electrodes reported to date are exclusively synthesized by using petroleum-derived chemicals, undoubtedly enhancing the cost of large-scale production applications. Therefore, seeking low-cost and abundant carbon sources to fabricate carbon-based materials for high-performance CDI is still highly requested.…”
Section: Introductionmentioning
confidence: 99%
“…The electrosorption performance of CNTs electrodes fabricated using different methods was investigated by batch-mode electrosorption experiments with a continuously recycling system [21].…”
Section: Batch-mode Electrosorption Experimentsmentioning
confidence: 99%